2013
DOI: 10.2298/mpns1304153s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and length of service on the level of stress and burnout syndrome

Abstract: Age and length of service have important influence on the level of stress and burnout syndrome: the older the physicians and the higher the length of service the higher the level of stress and the higher the risk of burnout syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 11 publications
3
23
2
4
Order By: Relevance
“…found among the oldest physicians with the greatest length of service, whereas the lowest levels were found among the youngest physicians with the shortest length of service (8). In contrast, our research showed no correlations between length of service and burnout and age and burnout.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…found among the oldest physicians with the greatest length of service, whereas the lowest levels were found among the youngest physicians with the shortest length of service (8). In contrast, our research showed no correlations between length of service and burnout and age and burnout.…”
Section: Resultscontrasting
confidence: 92%
“…They may feel malaise and have undefined physical pains for longer periods of time (headaches, back pain, insomnia, upset stomach, etc.) (8). Given these symptoms of burnout, it is inevitable that the consequences will be manifested through negative work attitudes, low levels of performance (9,10), low productivity, absenteeism and job turnover (11,12), and these results have been found in all types of organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The same was found in the research of Stanetić and Teŝanović (2013), which was conducted by medical staff, although the opposite has also been found in other researches (Vredenburgh et al 1999;Hamama 2012). The specific finding of the present study could be interpreted by the prolonged age, by which their families are financially supporting many young people in Greece.…”
supporting
confidence: 83%
“…Emotional workload in younger people and lack of social support in older employees were associated with a higher risk of mental health complaints [15]. Older age and longer length of service were also associated with higher levels of stress and emotional exhaustion in a group of family physicians [16]. Low occupational status and educational level were associated with higher work-related stress risk in a large sample of French workers [17].…”
Section: Introductionmentioning
confidence: 99%